Peyer's patches are required for oral tolerance to proteins - Fujihashi, Kohtaro (The National Academy of Sciences, 2001)
To clarify the role of Peyer's patches in oral tolerance induction, BALB/c mice were treated in utero with lymphotoxin β-receptor Ig fusion protein to generate mice lacking Peyer's patches. When these Peyer's patch-null mice were fed 25 mg of ovalbumin (OVA) before systemic immunization, OVA-specific IgG Ab responses in serum and spleen were seen, in marked contrast to low responses in OVA-fed normal mice. Further, high T-cell-proliferative- and delayed-type hypersensitivity responses were seen in Peyer's patch-null mice given oral OVA before systemic challenge. Higher levels of CD4(+) T-cell-derived IFN-γ, IL-4, IL-5, and IL-10 syntheses were noted in Peyer's patch-null mice fed OVA, whereas OVA-fed normal mice had suppressed cytokine levels. In contrast, oral administration of trinitrobenzene sulfonic acid (TNBS) to Peyer's patch-null mice resulted in reduced TNBS-specific serum Abs and splenic B cell antitrinitrophenyl Ab-forming cell responses after skin painting with picryl chloride. Further, when delayed-type hypersensitivity and splenic T cell proliferative responses were examined, Peyer's patch-null mice fed TNBS were unresponsive to hapten. Peyer's patch-null mice fed trinitrophenyl-OVA failed to induce systemic unresponsiveness to hapten or protein. These findings show that organized Peyer's patches are required for oral tolerance to proteins, whereas haptens elicit systemic unresponsiveness via the intestinal epithelial cell barrier.